AB0183 The evaluation of clinical evaluation for disease activity of rheumatoid arthritis. (23rd January 2014) - Mukai, M.; Kanda, M.; Kondo, M.
Abstract : Background: The activity of rheumatoid arthritis (RA) is evaluated with many clinical criteria such as DAS (disease activity score), SDAI (simplified disease activity index), CDAI (clinical disease activity), and Boolean method. With these criteria, it has become convenient to evaluate the patient's state and the efficacy of treatment for RA. However, the subjective data such as patient global assessment have sometimes no connection to the objective data. Objectives: The purpose is to evaluate the each clinical scale to find the difference of clinical efficacy, and to find main factor that causes the discrepancy of the criteria from clinical state of the patients. Methods: We retrospectively evaluated 421 patients with RA, who had been followed in our division in August 2012, with clinical criteria such as DAS28ESR, DAS28CRP, SDAI, CDAI, and Boolean method (trial and practice). The ratio of male to female was 83:338, and the average age was 64.4±13.5 (17.2-91.9) years old. The average follow-up periods in our division was 8.4±5.5 (0.2-29.0) years. Results: Methotrexate and biologics were administered in 301 (71.5%) and 148 (35.2%) patients, respectively. Steroid was used in 164 patients (39.0%). Three hundreds twenty-seven patients (77.7%) were achieved to clinical remission with one of these criteria, whereas 103 patients (24.2%) were satisfied with all criteria for clinical remission. The ratio of clinical remission was much with DAS28CRP (67.2%), and little with Boolean trail (28.3%). Although more than 90% of patients showed low disease activity with SDAI and CDAI, only 69.3% patients were satisfied with low disease activity by DAS28ESR. The main factors not to satisfy clinical remission were patient's global assessment for all criteria, and ESR for DAS28ESR. Patient's visual analogue scales were not often reflected with their real clinical assessment by their words. As ESR was also reflected with anemia and hyper-gammaglobulinemia, it was not always useful to evaluate the inflammation of RA. The many patients with high disease activity had high score of tender joints count and patient global assessment without inflammation. Conclusions: Because of the progression of treatment for RA, many patients were achieved to the clinical remission or low disease activity in real world. The patients who showed high disease activity were mainly occupied with those who had destructive joints damage without inflammation. Also, it should be very careful to judge the patients' clinical state when the clinical remission criteria would not be satisfied because of the failure due to only the subjective marker. Disclosure of Interest: None Declared